Factors Correlated to the Renoprotective Effect of Sitagliptin in Patients with Type 2 Diabetes Mellitus: Retrospective Observational Study - Pirawan Khunkit; Konkanok Wattana (Advances in Pharmacological and Pharmaceutical Sciences)
Background. Sitagliptin functions similarly to GLP-1RAs by incretin and insulin secretion and has a renoprotective effect. Diabetic kidney disease (DKD) is a kidney complication that increases the mortality rate in type 2 diabetes mellitus (T2DM) patients. The important parameters that predict appropriate sitagliptin treatment are known as factors. This study aimed to assess factors that correlated with the renoprotective effect of sitagliptin in patients with T2DM. Methods. This retrospective study collected data from a tertiary hospital in Thailand. All T2DM patients who were treated with sitagliptin and had complete data were recruited to analyze the outcome. The primary outcome was a correlation between demographics, laboratory data, and kidney outcome. The secondary outcome was the different laboratory results between pre- and posttreatment of patients treated with sitagliptin. Results. The number of patients who were treated for T2DM with sitagliptin was 191. Only 102 patients had complete laboratory parameters. Results showed a positive correlation between baseline FBS, HbA1c, and Scr change (p value = 0.042 and 0.005) at 6 months and baseline age, TG, and Scr change (p value = 0.010 and 0.022) at 18 months; while a negative correlation was observed between baseline FBS, HbA1c, and eGFR change (p value = 0.017 and 0.007) at 6 months and baseline age and eGFR change (p value = 0.010) and between HDL-cholesterol and Scr change at 18 months (p value = 0.044). The eGFR stage 1 subgroup showed a positive correlation between baseline HbA1c and Scr change (p value <0.001) and baseline DM duration and eGFR change (p value = 0.004). Moreover, sitagliptin showed statistically significant FBS, HbA1c, LDL-cholesterol, and TC reduction. Furthermore, HDL-cholesterol showed statistically significant elevation. Conclusion. FBS, HbA1c, and age were factors that correlated with the renoprotective effect of sitagliptin. The eGFR ≥90.00 ml/min/1.73 m2 patients group showed a duration of DM in which factors correlated with renoprotective effect. Moreover, sitagliptin also can improve glucose levels and lipid profile.